Politics under the Weather: Droughts, Parties and Electoral Outcomes - Paulo Bastos; Sebastian Miller (Inter-American Development Bank (IDB), 2013)
The increased occurrence of extreme weather conditions leading to drought is a key development challenge. This paper studies how these extreme events interact with the political process at the local level using rich administrative data for drought declarations and mayoral elections in Brazil. While accounting for current and historical rainfall patterns, the paper finds that that: i) municipalities led by a mayor affiliated with the Presidents party are more likely to receive formal drought declarations prior to the municipal election; and ii) receiving a drought declaration reinforces the electoral advantage of incumbent mayors running for reelection. These results are robust to the inclusion of a rich set of controls for municipal attributes.
Keywords: D72; Q54; 330